Encyclopedia of Japanese martial arts - Hall, D. A. (Kodansha USA, 2012)
This authoritative and comprehensive encyclopedia is an invaluable resource for martial artists of all levels, scholars, researchers, institutions, and anyone interested In Japanese history and culture